A Guide to Civil Procedure : Integrating Critical Legal Perspectives - Porter, Elizabeth (Law teacher); Pedro, Portia; Malveaux, Suzette; Coleman, Brooke D. (Book collections on Project MUSE., 2022)
"This book represents our efforts, and the efforts of our contributors, to center questions of inequality in the teaching, learning, and practice of civil procedure by shining a light on the ways in which civil procedure may privilege-or silence-voices in our courts"--